1987
DOI: 10.1128/jb.169.9.4003-4010.1987
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide tightly bound to porin monomers and trimers from Escherichia coli K-12

Abstract: Lipopolysaccharide (LPS) bound to isolated porin was detected on polyacrylamide gels by using a carbohydrate-specific silver stain and on Western blots by using anti-lipid A monoclonal antibodies. Porin was isolated from Escherichia coli JF733 (Ra chemotype) and D21f2 (Re chemotype). Isolated porin was separated from loosely associated LPS by polyacrylamide gel electrophoresis (PAGE) in sodium dodecyl sulfate (SDS). Unheated porin traveled on gels as aggregates, presumably trimers, with an apparent molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 41 publications
2
53
0
Order By: Relevance
“…For external cell surface residues, associations with the core and G-antigen sugars of LPS may exert further requirements for hydrophilicity. Polypeptides that traverse the OM bilayer, on the other hand, associate with phospholipid and LPS fatty acids (54,62) and must therefore include residues of sufficient hydrophobicity to stabilize this interaction. Enteric bacterial porins, for example, contain transmembrane ,B-strands that possess a hydrophobic face that interacts with the OM lipids on the porin exterior and a hydrophilic face that lines the surface of the water-filled channel in the porin interior (11,35,68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For external cell surface residues, associations with the core and G-antigen sugars of LPS may exert further requirements for hydrophilicity. Polypeptides that traverse the OM bilayer, on the other hand, associate with phospholipid and LPS fatty acids (54,62) and must therefore include residues of sufficient hydrophobicity to stabilize this interaction. Enteric bacterial porins, for example, contain transmembrane ,B-strands that possess a hydrophobic face that interacts with the OM lipids on the porin exterior and a hydrophilic face that lines the surface of the water-filled channel in the porin interior (11,35,68).…”
Section: Discussionmentioning
confidence: 99%
“…SDS-PAGE was performed and analyzed by ammoniacal silver staining as described previously (35,51). Cell envelopes and OM fractions from wild isolates of Salmonella, Citrobacter, Serratia, and Enterobacter resolved poorly in SDS-PAGE, probably because of the association of OM proteins with LPS (54,62) and capsule. The incubation of OM or cell envelopes with lysozyme (1 mg/ml) for 30 min at 0°C and the addition 0.03 M EDTA and 0.2 M NaCl to the SDS-PAGE sample buffer improved electrophoretic separation.…”
Section: Methodsmentioning
confidence: 99%
“…Hib, Haernophilus influenzae type b; mAb, monoclonal antibody; LPS, lipopolysaccharide; CD, circular dichroism; FPLC, fast protein liquid chromatography; PAGE, polyacrylamide gel electrophoresis; ELISA, enzyme-linked immunosorbent assay; PBS, phosphate-buffered saline Porins of Gram-negative bacteria bind tightly to lipopolysaccharide (LPS) [7,8]. Purified OmpF of E. coli was shown to have up to nine molecules of LPS associated with each trimer [8,9]. While most of this LPS was loosely bound and easily dissociated, it was estimated that one LPS molecule remained tightly bound to each OmpF trimer [9].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that several trimeric forms exist after cell solubilization. Moreover, immunological differences between these native forms have been demonstrated using antibodies directed against lipopolysaccharide [27] and against OmpF [32]. In addition, it has been demonstrated that several monoclonal antibodies prepared against the unfolded monomer of OmpC and OmpF cannot recognize the OmpF trimer, indicating the masking of these epitopes in the native form [33].…”
Section: Discussionmentioning
confidence: 99%